1990
DOI: 10.1017/s0022149x00011974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flubendazole on the number of first-stage larvae of Angiostrongylus cantonensis released in the faeces of treated rats

Abstract: The effect of flubendazole orally administered at 10 mg/kg/day for 5 consecutive days (the 11th, 20th or 40th post-infection) on the number of first-stage larvae (L1) of Angiostrongylus cantonensis released in the faeces of rats each infected with 40 third-stage larvae was determined. Faecal examination for 5 months, the period from medication to dissection of rats, showed that L1 release ceased in all the rats of medicated groups by about 1 week after the termination of dosing and resumed 1–2 months later in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…MAKI & YANAGISAWA 31 determined the effect of flubendazole po administered at 10 mg/kg/day for five consecutive days (the 11 th ; 20 th or 40 th post-infection) on the number of first-stage larvae of Angiostrongylus cantonensis, released in the faeces of rats. Faecal examination for five months showed that L1 release ceased one week after conclusion of treatment and resumed one to two months later in 86% of the rats.…”
Section: Chemotherapy Before Worm Maturationmentioning
confidence: 99%
“…MAKI & YANAGISAWA 31 determined the effect of flubendazole po administered at 10 mg/kg/day for five consecutive days (the 11 th ; 20 th or 40 th post-infection) on the number of first-stage larvae of Angiostrongylus cantonensis, released in the faeces of rats. Faecal examination for five months showed that L1 release ceased one week after conclusion of treatment and resumed one to two months later in 86% of the rats.…”
Section: Chemotherapy Before Worm Maturationmentioning
confidence: 99%